The Thoughts and Movements of Gakwah Kh. Abdul Muin Yusuf in Sidenreng Rappang Regency - Hendra; Nurhidayat Muhammad Said; St. Nasriah (Jurnal Mercusuar, 2022)
This research aims to examine, analyze, and reveal the Movements and Thoughts as well as the messages of Islamic preaching by KH. Abdul Muin Yusuf in Sidenreng Rappang Regency. The main issues are: How are the thoughts and preaching movements carried out by Anregurutta K.H. Abdul Muin Yusuf in Sidenreng Rappang Regency? This research is a qualitative descriptive study using a preaching approach. The data collection methods used are observation, interviews, and documentation. Then, data processing and analysis techniques are carried out through three stages: data reduction, data display, and conclusion drawing. The results of this research indicate that: First, KH. Abdul Muin Yusuf has a concept of Cultural Preaching thought and uses the Book or Writing (Bil-Kitabah or Bil-Qalam) method of preaching. Meanwhile, the preaching movements of Anregurutta KH. Abdul Muin Yusuf encompass several aspects, namely; preaching movements as a religious scholar (Qadhi), Political Figure, and as an Educator.